2019
DOI: 10.1111/imj.14176
|View full text |Cite
|
Sign up to set email alerts
|

Risk versus regulation: an update on the state of e‐cigarette control in Australia

Abstract: E‐cigarettes are increasingly common around the world, particularly among youth. Ingestion of nicotine‐containing e‐liquid, while relatively rare, is the major toxicological risk associated with their use. Current Australian regulation has nicotine for use in e‐cigarettes listed as a dangerous poison in Schedule 7, with its supply or sale illegal in all states and territories, while regulation on the sale of e‐cigarettes and accessories varies by state. However, with increasing evidence that e‐cigarettes produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…respectively. [11][12][13] The 2017 Australian secondary students' alcohol and drug survey found that 13% of students had used an e-cigarette at least once. 14 Of the 2410 students who used an e-cigarette, 48% reported that they had never smoked a traditional tobacco cigarette before using an e-cigarette.…”
Section: Author Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…respectively. [11][12][13] The 2017 Australian secondary students' alcohol and drug survey found that 13% of students had used an e-cigarette at least once. 14 Of the 2410 students who used an e-cigarette, 48% reported that they had never smoked a traditional tobacco cigarette before using an e-cigarette.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…All rights reserved prescription for personal use. 11 The sale of e-cigarettes to people aged under 18 years is also illegal. 11 In practice, however, a 2015 survey of Australian e-cigarette use found that 90% of users purchased e-cigarettes and liquids from unregulated online stores.…”
Section: Author Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Nicotine-containing e-fluids are already classified as a Schedule 7 substance in Australia, which means they are illegal to possess without a prescription from a medical professional. 3 If the proposed bans are enforced, from 1 January 2021, individuals will no longer be allowed to import nicotinecontaining e-fluids for use in e-cigarettes, even if they have a prescription. Only general practitioners or pharmacies with appropriate permits in place will be permitted to import or supply these e-fluids.…”
mentioning
confidence: 99%